Substantiation of the methodology for adaptive formation of the mining work schedule taking into account the variable quality of ore raw materials and market dynamics - Y.I. Hryhoriev (Технічна інженерія, 2025)
One of the most urgent tasks of modern mining production is to ensure the stability and adaptability of the mining operation schedule in stochastic management conditions. The paper substantiates an approach to building a calendar plan based on optimizing the position of the averaging line of the mining operation schedule in the three-dimensional coordinate space of the mining mass, the cut-off grade of the useful component and the ore volume. The aim of the research is to develop a method for adaptive formation of the mining schedule taking into account the dynamics of the price of the mining enterprise’s products, as well as the variable quality of ore raw materials. The methodological basis is the optimization of the provisions of the averaging straight line schedule of the mining schedule, the interpolation of three-dimensional limiting surfaces, previously implemented by the graph-analytical method. The algorithm is implemented in Python in the Google Colaboratory environment using the SciPy and Plotly libraries for optimization and visualization of results, respectively. The proposed approach allows us not only to ensure compliance of the scope of work with the limitations of the laws of development of the open-pit working area, but also to minimize the costs of opening in changing market conditions. The results of the study have scientific value for the further development of methods for dynamic design of open pit mining of mineral deposits. The practical significance of the research results lies in the possibility of using the proposed methodology to optimize the mining operations of mining enterprises in a stochastic economic environment.